2015
DOI: 10.1016/j.tem.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Vascular function, insulin action, and exercise: an intricate interplay

Abstract: Insulin enhances the compliance of conduit arteries, relaxes resistance arterioles to increase tissue blood flow and dilates precapillary arterioles to expand muscle microvascular blood volume. These actions are impaired in the insulin resistant states. Exercise ameliorates endothelial dysfunction and improves insulin responses in insulin resistant patients, but the precise underlying mechanisms remain unclear. The microvasculature critically regulates insulin action in muscle by modulating insulin delivery to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 98 publications
2
58
0
2
Order By: Relevance
“…In this regard, several studies showed that insulin induces changes in microvascular vasomotion, promotes capillary recruitment and NO synthesis . The binding of insulin to its receptor on endothelium could lead to the activation of eNOS pathway and vasodilation . These observations can be useful to explain the results obtained in our study after consuming breakfast.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In this regard, several studies showed that insulin induces changes in microvascular vasomotion, promotes capillary recruitment and NO synthesis . The binding of insulin to its receptor on endothelium could lead to the activation of eNOS pathway and vasodilation . These observations can be useful to explain the results obtained in our study after consuming breakfast.…”
Section: Discussionsupporting
confidence: 61%
“…36,37 The binding of insulin to its receptor on endothelium could lead to the activation of eNOS pathway and vasodilation. 38,39 These observations can be useful to explain the results obtained in our study after consuming breakfast.…”
Section: Discussionsupporting
confidence: 58%
“…In humans, a meta-analysis of genome-wide association studies showed a relationship between angiogenesis and insulin resistance, further supporting the notion that chronic tissue ischemia has an important role in insulin resistance (Shungin et al, 2015). Engaging VEGFB/VEGFR1 to improve perfusion in skeletal muscle and liver, in addition to adipose tissue, could be of further benefit for type 2 diabetic patients (Zheng and Liu, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…This suggests that endothelial function changes are related to greater glucose utilization. We acknowledge while this later observation may seem counter‐intuitive at first, the reduction in FMD iAUC 120min may be due to the preservation of fasting FMD with exercise training (Das et al, ) or a re‐distribution of blood flow away from the brachial artery toward the microvasculature for increased delivery and use of glucose by skeletal muscle (Zheng and Liu, ). Indeed, it was recently demonstrated that resistance exercise training improved microvascular blood flow during an oral glucose load in obese adults with type 2 diabetes and this was independent of changes in postprandial FMD (Russell et al, ).…”
Section: Discussionmentioning
confidence: 99%